The effect of sulfate ion on the isomerization of n-butane to iso-butane - Triwahyono, Sugeng (Kexue Chubaneshe/Science Press, 2006)
The effect of sulfate ion (SO2-4) loading on the properties of Pt/SO2-4-ZrO2 and on the catalytic isomerization of n-butane to iso-butane was studied. The catalyst was prepared by impregnation of Zr(OH)4 with H2SO4 and platinum solution followed by calcination at 600 Â°C. Ammonia TPD and FT-IR were used to confirm the distribution of acid sites and the structure of the sulfate species. Nitrogen physisorption and X-ray diffraction were used to confirm the physical structures of Pt/SO2-4-ZrO2. XRD pattern showed that the presence of sulfate ion stabilized the metastable tetragonal phase of zirconia and hindered the transition of amorphous phase to monoclinic phase of zirconia. Ammonia TPD profiles indicated the distributions of weak and medium acid sites observed on 0.1 N and 1.0 N sulfate in the loaded catalysts. The addition of 2.0 N and 4.0 N sulfate ion generated strong acid site and decreased the weak and medium acid sites. However, the XRD results and the specific surface area of the catalysts indicated that the excessive amount of sulfate ion collapsed the structure of the catalyst. The catalysts showed high activity and stability for isomerization of n-butane to iso-butane at 200 Â°C under hydrogen atmosphere. The conversion of n-butane to iso-butane per specific surface area of the catalyst increased with the increasing amount of sulfate ion owing to the existence of the bidentate sulfate and/or polynucleic sulfate species ((ZrO)2SO2), which acts as an active site for the isomerization.